Impact of agricultural activities-motor vehicles and e-waste on sediment characteristics of the Serin River, Malaysia - Ling, Teck Yee; Cornellia, Murek; L., Nyanti (2009)
Sediment is a sink for organic materials, nutrients and heavy metals and sediment condition affects the overlying water. Though Serin River is a source of drinking water, agricultural and waste disposal activities in the watershed may impact the sediment of the river. Therefore, the objective of this study was to investigate the organic matter, nutrients and heavy metals in the sediment of the Serin River. Five stations were selected for sediment sample collection. Results of the study show that organic matter (OM) ranged from 0.7% to 5.9%, TP was 100·366 (mglkg), TAN was 16-141 (mg/kg), TON was 550-3019(mg/kg), and TKN was 566-3160 (mg/kg). Sediment oxygen demand (SOD20) ranged from 5.6 to 14.2 (g Oim2/d). Among the five stations OM, TKN, and SOD of the sediment were second highest at the two stations downstream of animal (fish, chicken and pig) farming. TP and TAN were the second highest at the station downstream of fish farming and third highest at the station downstream of pig farming. Zn, Cu and Cd ranged from 132-357 (mg/kg), 26.7-96.7 (mg/kg) and 4.0.19.3(mg/kg). According to USEPA guideline, sediments at four stations were heavily polluted with Zn, Cu and Cd whereas the station that was farthest upstream, near a village, was slightly polluted with Zn and Cu. This study indicates that animal farming has an impact on the organic matter content, nutrients (N and P), oxygen demand and heavy metals of the sediment. Motor vehicles and discarded e-waste also contributed to the heavy metals in the sediment. Farm effluents and storm water should be treated and e-waste recycled to protect the water quality of the river for its designated use.